Laquinimod Delays and Suppresses Nephritis in Lupus‐Prone Mice and Affects Both Myeloid and Lymphoid Immune Cells. Issue 3 (March 2014) - Lourenço, Elaine V.; Wong, Maida; Hahn, Bevra H.; Palma‐Diaz, M. Fernando; Skaggs, Brian J.
<x xml:space="preserve">Abstract</x> Objective Lupus nephritis depends on autoantibody deposition and activation of multiple immune cell types that promote kidney inflammation, including lymphocytes and monocyte/macrophages. Laquinimod, currently in clinical trials for multiple sclerosis and lupus nephritis, reduces infiltration of inflammatory cells into the spinal cord in experimental autoimmune encephalomyelitis. Activated monocyte/macrophages infiltrate the kidneys during nephritis in systemic lupus erythematosus (SLE). We undertook this study to determine whether using laquinimod to reduce monocyte/macrophage‐driven tissue damage as well as to alter lymphocytes in SLE nephritis could have greater therapeutic benefit than current treatments that primarily affect lymphocytes, such as mycophenolate mofetil (MMF). Methods To test laquinimod efficacy, we used the (NZB × NZW)F1 mouse model of SLE, in which disease manifests as nephritis. Preventive and therapeutic studies were performed to determine whether laquinimod could prevent or delay nephritis, as measured by proteinuria, serum creatinine, survival, and renal pathology. Spleen and kidney leukocyte populations and suppression assays were analyzed by flow cytometry. Results Laquinimod prevented or delayed lupus manifestations at levels equal to or better than MMF. Laquinimod treatment was associated with reduced numbers of monocyte/macrophages, dendritic cells, and lymphocytes, as well as with induction of myeloid‐derived suppressor cells in spleens and kidneys. Laquinimod suppressed macrophage‐secreted tumor necrosis factor α and induced production of interleukin‐10 (IL‐10). In addition, laquinimod suppressed interferon‐γ and IL‐17 production by lymphocytes and down‐regulated expression of activation/costimulatory markers on antigen‐presenting cells. Conclusion The effects of laquinimod on myeloid and lymphoid cells may contribute to improvements in (NZB × NZW)F1 mouse survival, proteinuria, and glomerulonephritis. Future development of laquinimod as a therapeutic agent for lupus nephritis is promising.